mRNA decay mediated by two distinct AU-rich elements from c-fos and granulocyte-macrophage colony-stimulating factor transcripts: different deadenylation kinetics and uncoupling from translation. - Chen, C Y (1995)
Poly(A) tail removal is a critical first step in the decay pathway for many yeast and mammalian mRNAs. Poly(A) shortening rates can be regulated by cis-acting sequences within the transcribed portion of mRNA, which in turn control mRNA turnover rates. The AU-rich element (ARE), found in the 3' untranslated regions of many highly labile mammalian mRNAs, is a well-established example of this type of control. It represents the most widespread RNA stability determinant among those characterized in mammalian cells. Here, we report that two structurally different AREs, the c-fos ARE and the granulocyte-macrophage colony-stimulating factor (GM-CSF) ARE, both direct rapid deadenylation as the first step in mRNA degradation, but by different kinetics. For c-fos-ARE-mediated decay, the mRNA population undergoes synchronous poly(A) shortening and is deadenylated at the same rate, implying the action of distributive or nonprocessive ribonucleolytic digestion of poly(A) tails. In contrast, the population of granulocyte-macrophage colony-stimulating factor ARE-containing mRNAs is deadenylated asynchronously, with the formation of fully deadenylated intermediates, consistent with the action of processive ribonucleolytic digestion of poly(A) tails. An important general implication of this finding is that different RNA-destabilizing elements direct deadenylation either by modulating the processivity at which a single RNase functions or by recruiting kinetically distinct RNases. We have also employed targeted inhibition of translation initiation to demonstrate that the RNA-destabilizing function of both AREs can be uncoupled from translation by ribosomes. In addition, a blockade of ongoing transcription has been used to further probe the functional similarities and distinctions of these two AREs. Our data suggest that the two AREs are targets of two distinct mRNA decay pathways. A general model for ARE-mediated mRNA degradation involving a potential role for certain heterogeneous nuclear ribonucleoproteins and ARE-binding proteins is proposed.